Intramuscular Pethidine for Pain Relief in the First Stage of Labor - Sharmin, Saria; Khanam, Shafeya; Saha, Samar Chandra; Naher, Fatema Kamrun; Jahan, Mafruha; Shukla, Joyutpala; Chowdhury, Akhtari Hossain; Ashafuddoula, Ahmed (Ibrahim Cardiac Medical Journal, 2019)
Objective: The objective of this study was to see the efficacy of intramuscular pethidine for pain relief in the 1st stage of labor. Methods: This prospective study was carried out in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka from April 2005 to December 2005. Age and parity matched 80 pregnant women were recruited in the study and were divided equally in experimental and palcebo groups (40 in each group). The Experimental group received intramuscular Inj. Pethidine HCI 1.5 mg/kg body weight in 2 ml with Inj. metoclopramide 12.5 mg and the Placebo group received 2 ml intramuscular normal saline. The intervention was started at active first stage of labor with cervical dilatation of 3-4 cm and when patients requested for analgesia. Pain was assessed at the highest point of pain at 15- and 30-minute intervals using 100 mm visual analogue scale (VAS) and patients were asked to give a verbal categorical rating of their pain as "a lot better", "a little better", "much the same", "a little worse", or "much worse". Level of sedation was also assessed at the same intervals. Details of labor, including cervical dilatation before and after analgesia, mode of delivery, duration of injection to delivery time and assessment of neonates by APGAR score at one and five minutes were recorded. Result: All the baseline characteristics like maternal age, body surface area (BSA), parity, gestational age of the subjects between the Experimental and Placebo groups were almost identical. All the intrapartum variables like baseline cervical dilatation, VAS pain score, VAS sedation score and injection to delivery interval were also found to be fairly comparable between groups. At 15 minutes interval more than one-quarter (27.5%) of the Experimental group got mildly drowsy, while none of the Placebo group changed from their baseline status. At 30 minutes interval 27.5% were mildly drowsy, 22.5% were moderately drowsy and 1 (2.5%) was asleep in the Experimental group, while all of the Placebo group subjects were alert as before. The groups were quite different in respect to level of sedation following intervention (p < 0.001). Nearly three quarters (72.5%) of the Experimental group had VAS pain score at 30 minutes interval at or below median level, whereas only 25% of the Placebo group had the same level at same interval (p < 0.001). The Experimental group had a significantly lower demand for further analgesia (50%) compared to the Placebo group (80%) (p=0.005). However, 15 (37.5%) subjects of the Experimental group experienced nausea and or vomiting, whereas none of the Placebo group had such experience (p<0.001). Majority (82.5%) of the Experimental group and 75% of the Placebo group had normal delivery. The comparison of foetal outcome in terms of APGAR score at 1 and 5 minutes, oxygen needed and NICU admission required for resuscitation revealed no significant difference between the groups with respect to any of these variables (p<0.05). Conclusion: The intramuscular Pethidine is significantly effective at providing analgesia in pregnant women in 1st stage of labor. The findings support the continued use of pethidine as a simple and cheap therapeutic option in the management of labor pain. Ibrahim Card Med J 2017; 7 (1&2): 99-106